2017
DOI: 10.1007/s11356-017-0787-3
|View full text |Cite
|
Sign up to set email alerts
|

How tapeworm infection and consumption of a Cd and Zn hyperaccumulating plant may affect Cu, Fe, and Mn concentrations in an animal—a plant consumer and tapeworm host

Abstract: This study evaluated the effects of a hyperaccumulator plant (Arabidopsis halleri), containing surplus of cadmium (Cd) and zinc (Zn) and being an admixture to the rat feed, on concentrations of copper (Cu), iron (Fe), and manganese (Mn) in the tissues of experimental rats infected/uninfected with the tapeworm (Hymenolepis diminuta). Male Wistar rats were divided into three groups (00, P0, and PT); the P0 and PT animals were fed a standard mixture for rats (ST-1) supplemented with the plant A. halleri at a week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This study expands our previous knowledge of the effects of Zn/ Cd hyperaccumulating plant A. halleri on rat organism (Jankovská et al, 2016;Jankovská, Sloup, Szaková, Magdálek, Nechybová, et al, 2018) and examines effects of new factors influencing the physiology of these experimental animals. These factors are the overdose of zinc lactate in the diet, and the combination of various diets with infection with the rat tapeworm H. diminuta.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This study expands our previous knowledge of the effects of Zn/ Cd hyperaccumulating plant A. halleri on rat organism (Jankovská et al, 2016;Jankovská, Sloup, Szaková, Magdálek, Nechybová, et al, 2018) and examines effects of new factors influencing the physiology of these experimental animals. These factors are the overdose of zinc lactate in the diet, and the combination of various diets with infection with the rat tapeworm H. diminuta.…”
Section: Discussionmentioning
confidence: 76%
“…it was reported that heavy metal absorption in the digestive tract of hosts is affected by certain intestinal helminths (Sures, 2004); this is primarily true for tapeworms and acanthocephalans, which utilize their metabolically active body surface (tegument) to absorb nutrients (Sures, 2004;Sures & Reimann, 2003). In other studies (Jankovská et al, 2016;Jankovská, Sloup, Szaková, Magdálek, Nechybová, et al, 2018), we worked with a Zn/Cd hyperaccumulating plant (Arabidopsis halleri, Brassicaceae) and monitored how its consumption can affect rat organism. The current study aimed to determine the effects of zinc, and to a lesser extent also cadmium (in feed), on the biochemical parameters in laboratory rats infected and/or uninfected with a tapeworm.…”
mentioning
confidence: 99%
“…Compared with uninfected rats, faecal excretion of cadmium and zinc was lower in H. diminuta -infected rats whose diet was supplemented with A. helleri , possibly because H. diminuta actively absorbs these trace elements (Sloup et al 2018). Moreover, tapeworms from rats fed this plant also bioaccumulated manganese relative to rat muscle concentrations, but iron concentration was lower in the tapeworm than in all tested host tissues (Jankovská et al 2018).…”
Section: The Parasite Lensmentioning
confidence: 99%
“…Since gastrointestinal helminths (including tapeworms) are present in the digestive tract, they can influence zinc metabolism significantly. According to many authors, tapeworms of the genus Hymenolepis can accumulate significant amounts of metal ions taken up by the host (Sures et al, 2002;Jankovská et al, 2018). Our study, therefore, focused on comparing the levels of zinc ingested and excreted by rats infected with tapeworms to those ingested and secreted by uninfected rats.…”
Section: Introductionmentioning
confidence: 99%